Sistem Pelaporan Pengolahan Sampah Berbasis Web Pada Dinas Lingkungan Hidup Kota Metro - Wulandari, Ika Arthalia; Widodo, Suyud (Jurnal Ilmiah Sistem Informasi (JISI), 2022)
The barrier to cleanliness in the environment is garbage that causes environmental pollution and will eventually damage the environment. So far, waste processing is carried out in a conventional manner, namely collection, transportation and final disposal at the final disposal site (TPA). Waste data processing includes data on achievement of waste reduction, data on achievements in reducing waste and producing a waste processing balance. Waste processing is very important for Metro City Environmental Service because it becomes an annual report submitted to the Mayor of Metro. Currently all waste processing data is conducted by using the Microsoft Excel program. Because the waste processing data are interrelated, it is very possible for processing with the application because it will be able to integrate the data, and formulas can be made in coding to avoid changing formulas when done in Excel, and it is made only once. The applications built is web-based with a structured programming approach, software development methods using SDLC Method. Software testing is using black box testing. Based on these problems, an application that can help process waste data processing at the Metro City Environmental Service is needed.